Suitability of three different legumes for Acanthoscelides obtectus development and population growth - Sonja Gvozdenac; Aleksandra Ilić; Mirjana Vasić; Snežana Tanasković; Dejan Prvulović (Journal of Central European Agriculture, 2023)
Legumes are a rich source of valuable nutrients thus represent important component in human and animal nutrition. The most important and often a limiting factor in legume production is the presence of seed pests, such as the bean weevil Acanthoscelides obtectus (Say, 1831). This work tested the suitability of three different legume species (common bean, faba bean and grass pea), the species with a growing interest in the human diet, for the development of the bean weevil, aiming to provide a reliable forecast of its population growth. After four months, been weevils consumed the highest percentage of the common bean kernels (70.79%), followed by the grass pea (53.13%), and faba bean (0.42%). The progeny production and population growth were significantly affected by the tested legume species. After each month, the total number of adults was the highest on the common bean, indicating its best suitability for the weevil’s development. Based on the number of the emerged specimens after each month of the observation, the bean weevil development was unhampered and continuous also on the grass pea. The lowest number of emerged adults, in all observation periods, was in faba bean, indicating its low preference and suitability for the weevil’s development. The population growth of the bean weevil was the highest on the common bean, followed by grass pea, and it fitted best to the quadratic equation model that enabled the prediction of the population growth of the bean weevil for each legume species in the next generations.